2008
DOI: 10.1523/jneurosci.3948-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Synaptic Input and the Timing of Gamma-Frequency-Modulated Firing of Pyramidal Cells during Neocortical “UP” States

Abstract: Gamma (␥) oscillation, a hallmark of cortical activity during sensory processing and cognition, occurs during persistent, self-sustained activity or "UP" states, which are thought to be maintained by recurrent synaptic inputs to pyramidal cells. During neocortical "UP" states, excitatory regular spiking (RS) (pyramidal) cells and inhibitory fast spiking (FS) (basket) cells fire with distinct phase distributions relative to the ␥ oscillation in the local field potential. Evidence suggests that ␥-modulated RS 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 50 publications
5
47
0
Order By: Relevance
“…Gamma-band synchronization within a local group of neurons entails rhythmic inhibition through the local inhibitory interneuron network (Csicsvari et al, 2003;Hasenstaub et al, 2005;Vida et al, 2006;Buzsáki, 2006;Bartos et al, 2007;Morita et al, 2008). The gamma-rhythmic inhibition constitutes a gamma cycle that might impact neuronal processing .…”
Section: Introductionmentioning
confidence: 99%
“…Gamma-band synchronization within a local group of neurons entails rhythmic inhibition through the local inhibitory interneuron network (Csicsvari et al, 2003;Hasenstaub et al, 2005;Vida et al, 2006;Buzsáki, 2006;Bartos et al, 2007;Morita et al, 2008). The gamma-rhythmic inhibition constitutes a gamma cycle that might impact neuronal processing .…”
Section: Introductionmentioning
confidence: 99%
“…They have an intrinsic resonance near these frequencies, which is evident in their minimum repetitive firing rate of 10 -30 spikes/s (Golomb et al 2007;Tateno et al 2004). Feedback excitation of cortical FS cells during persistent activity engages this resonance (Hausenstaub et al 2005;Morita et al 2008) to produce oscillatory inhibition in the cortex. Because of these properties, cortical FS cells are easily synchronized by noisy shared synaptic excitation and gap junctions (Galaretta and Hestrin 1999; Gibson et al 1999;Mancilla et al 2007;Tateno and Robinson 2009).…”
mentioning
confidence: 99%
“…One hundred and two hundred active excitatory synapses, each with a mean firing frequency of 3 Hz, were distributed among the basal and distal dendrites, respectively. The presynaptic spikes that generate oscillatory inhibition have a default fixed average frequency summed over the whole population of inhibitory synapses of 2,000/s and follow a Gaussian-like phase distribution resembling that during in vivo gamma oscillations (Hasenstaub et al 2005;Morita et al 2008):…”
Section: Resultsmentioning
confidence: 99%
“…LTS cells have been shown to form an electrically coupled network via specific gap junctions (Gibson et al 1999), which is distinct from the network of fast spiking (FS) cells, another class of GABAergic interneurons, which, in contrast, selectively targets pyramidal somata and proximal dendrites. Several studies (Fanselow and Connors 2010;Fanselow et al 2008;Mancilla et al 2007;Vierling-Claassen et al 2010) have suggested that LTS cells can fire in synchrony at relatively slow frequencies (5ϳ30 Hz, around the -to ␤-frequency ranges), presumably by virtue of electrical coupling, again in contrast to the FS cells, which typically show synchronized firing in the ␥-frequency range (30ϳ80 Hz) (Buszsaki 2006;Fries 2009;Gouwens et al 2010;Hasenstaub et al 2005;Kopell and Ermentrout 2004;Morita et al 2008;Tateno et al 2004;Tiesinga and Sejnowski 2009;Wang and Buzsaki 1996;Whittington and Traub 2003). Cholinergic agonists induce beta oscillations in superficial layers of prefrontal cortical slices, which are independent of rhythms in the deeper layers (van Aerde et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation